The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1603/029.102.0405
|View full text |Cite
|
Sign up to set email alerts
|

Present Status of <I>Maconellicoccus hirsutus</I> (Hemiptera: Pseudococcidae) in the Mariana Islands and Its Control by Two Fortuitously Introduced Natural Enemies

Abstract: The mealybug Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae), attacks ornamental and fruit crops in the Mariana Islands. Insecticides cannot penetrate the heavy layers of wax that protect the insect's body. We surveyed the mealybug's locally recruited natural enemies and their effects on its population on Guam, Rota, Saipan, and Tinian to assess the need for introduction of exotic natural enemies. We monitored population densities of M. hirsutus, those of its natural enemies, and parasitism rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Of them, Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae) is a major pest of numerous economically important crops such as grapes, citrus, avocado, carambola, fig, guava, mango, sugarcane and mulberry; vegetable crops including asparagus, beans, beets, cabbage, peanuts, pigeon pea, cucumber, lettuce, pepper, pumpkin, and tomato; forest trees, many species of ornamental plants; and various fruits and shade trees in both tropical and subtropical countries (Hoy et al 2002;Kairo et al 2000;Reddy et al 2009;Roltsch et al 2006). M. hirsutus adults lay 300-600 eggs and complete the life cycle in 23-30 days with three (female) and four (male) nymphal instars (Hoy et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of them, Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae) is a major pest of numerous economically important crops such as grapes, citrus, avocado, carambola, fig, guava, mango, sugarcane and mulberry; vegetable crops including asparagus, beans, beets, cabbage, peanuts, pigeon pea, cucumber, lettuce, pepper, pumpkin, and tomato; forest trees, many species of ornamental plants; and various fruits and shade trees in both tropical and subtropical countries (Hoy et al 2002;Kairo et al 2000;Reddy et al 2009;Roltsch et al 2006). M. hirsutus adults lay 300-600 eggs and complete the life cycle in 23-30 days with three (female) and four (male) nymphal instars (Hoy et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Annual economic losses due to this pest have been estimated at approximately $2.5 million in Grenada, $5.1 million in Trinidad and $750 million in the United States, and to cause severe economic losses in Egypt and India (Kairo et al 2000). Reddy et al (2009) studied interactions of M. hirsutus and its natural enemies in Guam. Roltsch et al (2006) reported that two species of parasitoids reduced 98% of M. hirsutus density in southern California.…”
Section: Introductionmentioning
confidence: 99%
“…The low infestation rate of fruit was likely related to biological control by A. kamali. This parasitoid was likely introduced with M. hirsutus in Brazil (Marsaro Júnior et al 2013) and Colombia (Evans et al 2012;Rodríguez 2012), and has high specificity to M. hirsutus (Sagarra et al 2001) with high efficiency in its biological control (Michaud and Evans 2000;Roltsch et al 2006;Garcia-Valente et al 2009;Reddy et al 2009;IsiordiaAquino et al 2012).…”
mentioning
confidence: 99%
“…Much of the field research on managing M. hirsutus populations to date has been devoted to biological control, in particular on various parasitoids that in most cases have produced very effective control (Kairo et al 2000;Roltsch et al 2006;Reddy et al 2009). In contrast, most foliar insecticides have been ineffective at maintaining long-term suppression of M. hirsutus infestations.…”
Section: Discussionmentioning
confidence: 99%
“…Hall (1921) speculated that PHM arrived from India to Egypt around 1908 and spread rapidly within the country, causing damage to a leguminous food crop (Albizia lebbek), cotton (Gossypium hirsutum), and various ornamental plants. In 1983 it was discovered on the island of Hawaii in the Pacific and the following year on Guam (Reddy et al 2009). It is unknown how or when the leap to the Caribbean was made, but its establishment on most islands throughout the basin has occurred by colonizing over 150 species of tree and vegetable crops, ornamentals, and wild host plants as recorded in Trinidad alone (Sagarra and Peterkin 1999).…”
Section: Introductionmentioning
confidence: 99%